Exploring Graduates’ Attitudes on the Learning Environment and Institutional Development: A Case Study Based on Mixed Method - Mainali, Hari Lal; Kumar, Promod (Chaturbhujeshwar Academic Journal, 2024)
In the field of psychology, an attitude is commonly understood as a set of cognitive, emotional, and behavioral responses directed toward a specific object or situation. Guided by the fundamental principles of functional theory, this study aimed to explore graduates’ perceptions of their institution’s learning environment (LE) and institutional development (ID). The primary objective of this study was to assess graduates’ views on these two aspects. To achieve the objective, the study employed an exploratory and descriptive research design. A case study approach was utilized for qualitative data collection and subsequently analyzed thematically. For the quantitative aspect, statistical techniques such as cross-tabulations and chi-square tests were applied. The research was conducted using a convergent parallel model, combining both qualitative and quantitative methods. The findings revealed that graduates held generally unfavorable attitudes toward certain aspects of the learning environment, including library services, internship and placement opportunities, and teaching pedagogies. Notably, graduates from the BA program expressed more negative attitudes compared to those from other programs. Based on their feedback, graduates recommended that institutions should implement ICT-based teaching and learning activities, reduce external interference in educational processes, and invest in the capacity development of faculty members. Additionally, they suggested that the institution should provide ICT equipment to foster a technology-friendly environment, enhance library services by acquiring more books, and offer training in banking, insurance, and cooperative sectors to benefit students. The study’s conclusions provide valuable insights into graduates’ attitudes toward the learning environment and institutional development, providing clearer guidance for the management committee and administration of the CJMC. Furthermore, the findings offer important context for understanding the graduates’ suggestions and willingness to support institutional improvements.